A ampliação do tempo escolar em propostas de educação pública integral - SANTOS, Soraya Vieira (2009)
The increase of classroom time by means of the enacting of the proposals of full-time school period has been growing in public schools in Brazil. This paper, inserted in the Line of Cultural Research and Education Processes, has as its supposition that the change in the understanding and organization of the period is an essential part of a proposal of full time school sessions. Therefore, the objective is to analyze how the increase in the school period has been conceived in distinct proposals in full-time school in formation in Brazil, beginning with the promulgation of the Law of Directives and Basis of National Education in 1996. Within it are the proposals for full-time school sessions in 2008 in the public school systems, both state and municipal, as the More Education Program is presented by the federal government. In order to understand the everyday routine of a full-time school period, a Full-time Municipal School in the Goiania school district in Goias was chosen as the locus of the investigation, where field research was carried out by means of the analysis of documents, interviews and observation. The empirical research revealed that the central characteristic of the organization of time in the municipal full-time school is improvisation. The results reveal four fundamental characteristic for understanding the school period in the proposals of full-time school, which are: 1) a certain lack of responsibility by the state for public education, even though the increase in the time that the student stays in the school produces an apparent perception that the state is increasing its participation; 2) emphasis on the social risk for children and teenagers, so that the function of social welfare becomes incorporated into the responsibilities of the educational institution; 3) a distinction between full-time period and full-time education, based on the idea that it is not enough to offer a school with a full schedule, but it is necessary to offer whole education, that surpasses the school environment; 4) a search for a new model of school to heed the new social demands. These characteristics were discussed from the theoretic reference point of Gramsci and the contributions of Meszaros, having two central themes as a base, which are: the relationship between the State and civilian society, and full-time education in the perspective of educational innovation. The study suggests the need for understanding school as a right, in the perspective of contributing to the achievement of complete equality. Possibilities for continuing the investigations about this problem of full-time school in Brazil are suggested, considering that it is a current theme for the understanding of public schools in this country